2003
DOI: 10.1046/j.1095-8649.2003.00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐school positional preference and reduced tail beat frequency in trailing positions in schooling roach under experimental conditions

Abstract: Using three different swimming velocities and a school size of eight roach Rutilus rutilus, individual intra-school position and tail beat frequency were examined in a flume tank. Tail beat frequency was determined in defined leading and trailing positions. Individual roach showed consistent intra-school positional preferences which implied a sustained positional pattern where certain individuals took up front positions whereas other individuals swam in the rear part of the school. The positional preferences c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(102 citation statements)
references
References 55 publications
4
98
0
Order By: Relevance
“…Several previous studies have shown that swimming in a group decreases the cost of transport (Hartwell & Otto 1978, Fields 1990, Herskin & Steffensen 1998, Svendsen et al 2003, and a longer flume length increases U crit by allowing transition between swimming gaits (Peake & Farrell 2006, Tudorache et al 2007, 2010. Therefore, it is not surprising that U crit was significantly lower when post-smolts were tested individually in a smaller swim tunnel.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Several previous studies have shown that swimming in a group decreases the cost of transport (Hartwell & Otto 1978, Fields 1990, Herskin & Steffensen 1998, Svendsen et al 2003, and a longer flume length increases U crit by allowing transition between swimming gaits (Peake & Farrell 2006, Tudorache et al 2007, 2010. Therefore, it is not surprising that U crit was significantly lower when post-smolts were tested individually in a smaller swim tunnel.…”
Section: Discussionmentioning
confidence: 84%
“…U crit is normally measured using swimming respirometers containing individual animals. However, in a natural setting many species of fish form groups, which may significantly reduce the cost of transport; for example, the time to exhaustion increased 10-fold when swimming 6 men haden Brevoortia tyrannus together compared to swimming them alone (Hartwell & Otto 1978), while a reduction in tail-beat frequency of fish in trailing school positions has been observed in several studies (Fields 1990, Herskin & Steffensen 1998, Svendsen et al 2003. Thus, the U crit traditionally obtained from individual fish might not be a representative indicator for swimming capabilities in species forming schools or groups.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, small groups of Atlantic salmon swimming together in a larger volume may reduce stress levels during experiments. Swimming in schools is also likely to reduce the cost of transport and therefore improve the swimming performance in some species (Hartwell & Otto 1978, Herskin & Steffensen 1998, Svendsen et al 2003.…”
Section: Methodsmentioning
confidence: 99%
“…Tail beat frequency, which has been demonstrated to be positively correlated with oxygen consumption for solitary fish [35], is used as a proxy of the effort of the fish. Recent experiments on schools of roach [36] and seabass [35] found a significant reduction in tail beat frequency of the trailing fish compared with those of the front. However, because of the indirect nature of the measurement, there is still no conclusive proof of an energetic saving when swimming in school, and it is worth mentioning that many previous studies were confounded by the fact that fish in large groups tended to be less stressed, and thus may be expected to use less oxygen.…”
Section: Multi-scale Approaches Of Schooling Behaviourmentioning
confidence: 99%